2018
DOI: 10.3390/ijms19082300
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analyses of Root Restriction Effects on Phytohormone Content and Signal Transduction during Grape Berry Development and Ripening

Abstract: Phytohormones strongly influence growth, development and nutritional quality of agricultural products by modulating molecular and biochemical changes. The purpose of the present study was to investigate the influence of root restriction (RR) treatment on the dynamic changes of main phytohormones during the berry development and ripening of “Summer Black” early ripening seedless grape (Vitis vinifera × V. labrusca), and to analyze the changes in the biosynthesis and signal transduction pathways of phytohormones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 56 publications
9
17
0
Order By: Relevance
“…It has previously been shown that treatment with MeJA could induce lectin activity in the leaves of rice, barley, wheat and maize [76]. Studies have also shown that plant growth regulators, including phytohormones, could regulate plant responses to environmental stimuli [87,88]. MeJA activates a series of signal transduction pathways involved in plant responses to abiotic and biotic stresses, thereby enhancing stress tolerance [89].…”
Section: Plos Onementioning
confidence: 99%
“…It has previously been shown that treatment with MeJA could induce lectin activity in the leaves of rice, barley, wheat and maize [76]. Studies have also shown that plant growth regulators, including phytohormones, could regulate plant responses to environmental stimuli [87,88]. MeJA activates a series of signal transduction pathways involved in plant responses to abiotic and biotic stresses, thereby enhancing stress tolerance [89].…”
Section: Plos Onementioning
confidence: 99%
“…Interestingly, the variation tendency of SA concentrations was opposite to the variation tendency of ABA concentrations, indicating these two plant hormones might play a role at different stages of grapevine development. JA also has impact on increasing grapevine resistance to diseases, RR treatment could signi cantly develop JA concentration compared with control treatment 43 . As shown in the Fig.…”
Section: Analysis Of Different Physiological Parametersmentioning
confidence: 99%
“…Current studies have proved that the level of endogenous hormones in plants was not only affected by the climate 33 , but also by the cultivation environment and irrigation regime 34,43 . For examples, researchers found the ABA and ethylene signal components were differently accumulated in two distinct climates by analysing the transcriptional expression patterns of carotenoid metabolism in 'Cabernet Sauvignon' (Vitis vinifera L.) grapes 35 , further study also revealed that regulated de cit irrigation (RDI) could signi cantly improve ABA levels in 'Cabernet Sauvignon' (Vitis vinifera L.) wine grapes while reducing IAA levels 36 .…”
mentioning
confidence: 99%
“…Root restriction (RR) as a type of stress is a novel cultivation technique by restricting the root growth in a certain volume to improve the utilizing efficiency of agricultural resources [2,15]. Previous reports demonstrated that RR treatment limits the shoots and roots growth, increases the sugar content and the total and individual anthocyanin levels, promotes ascorbic acid and carotenoids accumulation, and accelerates the grape ripening process by changes in different phytohormones levels compared with the traditional cultivation (RC) [15][16][17][18][19][20]. Recently, our team annotated 291 metabolites in the table grape 'Red Alexandria' skin tissue while studying the growth processes using a non-targeted metabolomics method.…”
Section: Introductionmentioning
confidence: 99%